African Economic Growth 1900-50: Historical National Accounts for British Colonial Africa - Morten Jerven (African Economic History Network (AEHN), 2019)
The study of growth in African economies during the 20th Century is hampered by the lack of historical GDP estimates. There has been some backward projections, and country case studies, but despite the available data historical national accounts has not yet been assembled. This paper provides GDP estimates for some former British colonies between 1900 - 1950. The estimates indicate faster growth and economic expansion compared to the previous estimates that have been based on backward extrapolations. It further brings support to the argument that if we observe economic growth in many economies from the 1890s to the 1970s and then only interrupted from 1975s to 1995s, writing about the 20th century for Africa as a growth tragedy may be a mistake, caused by lack of data. New time series data on economic growth may foster a research agenda devoted to the study of different growth trajectories on the continent.
Keywords: C82; E01; N17; N37; 330; Africa; economic growth; national accounts; GDP